Adhesion of Streptococcus mitis and Fusobacterium nucleatum on nanopatterned titanium surfaces. Issue 3 (1st September 2013) - Su, Bo; SjÖstrÖm, Terje; Pang, James; Dymock, David
Abstract : Titania nanopillars with different heights and diameters (<100 nm) were patterned on titanium surfaces using a through-mask anodization technique. Two oral bacteria, that is, Streptococcus mitis (NCTC 10712) and Fusobacterium nucleatum (ATCC 25586), were used to study the bacterial attachment to nanopatterned titanium surfaces with and without saliva coating at different time points up to 4 h. The adhesion of both bacteria was decreased on 90-nm high nanopillars compared with both 15-nm high nanopillars and polished titanium surfaces, although this effect was significantly reduced with saliva coating, indicating a strong 'masking' effect of saliva on nanotopography-mediated bacterial adhesion. The results demonstrate that nanopatterning may be used to control bacterial attachment to titanium implant surfaces, but it is evident that for oral implant applications, saliva coating may reduce the desired topographical cues.